Idade de abate e condição sexual sobre o perfil de ácidos graxos na carne de bovinos - Carrilho, Charles de Oliveira (2018)
The objective of this work was to evaluate the fatty acid profile of steers from two categories (young and super-young), and two sex conditions (castrated and uncastrated), finished in feedlot. The experiment was conducted at the Fazenda Modelo Farm Station - IAPAR in Ponta Grossa, Paraná, in the year 2006. We used 32 animals from the genetic group ½ Purunã + ½ Canchim, as final live weight in kg of 518.17 young, 457.64 superyoung, 446.25 castrated and 529.56 non-castrated and fat thickness in mm of, 3.82 young, 4.86 super-young, 4.64 castrated and 4.04 non-castrated. The animals were fed a diet containing 11.2% crude protein and 3.07 Mcal digestible energy / kg dry matter (DM). The experimental design was completely randomized in a 2x2 factorial. The samples were taken from the Longissimus dorsi muscle between the 11th and 13th ribs of the left half carcass, after cooling. No significant interaction effect was observed between the variables. Shooting super-young animals instead of young animals, changes the profile of AGS, AGMI and AGPI, without influencing their totals. The unsaturated / saturated and polyunsaturated / saturated ratios were also not affected by the age of slaughter. The noncastration of steers, altered the AGS, AGMI and AGPI profile, with no effect on AGS and AGMI totals, and a higher amount of PUFA was observed and a higher polyunsaturated / saturated ratio was also observed to castrated animals when finished in feedlot.